Implementation of Integrated Curriculum in PAI Learning at SMK IT Nurul Fattah Banjar Margo, Tulang Bawang Regency - Saifudin Zuhri (Lembaga Yasin AlSys, 2025)
This study investigates the implementation of an integrated curriculum in Islamic Education (Pendidikan Agama Islam or PAI) at SMK Islam Terpadu (Integrated Islamic Vocational School) Nurul Fattah (Nufat), located in Banjar Margo, Tulang Bawang Regency. The research focuses on the planning, implementation, and evaluation of PAI learning that merges Islamic values with vocational competencies within a pesantren-based educational environment. Adopting a descriptive qualitative approach, data were collected through observation, in-depth interviews, and documentation. The findings reveal that lesson planning is conducted collaboratively, aligning Islamic values, pesantren vision, and multimedia skills. The learning implementation employs thematic, webbed, and ukhrawi models, integrating religious instruction with practical student activities, such as the production of digital da'wah content. Evaluation is carried out holistically, encompassing cognitive, affective, and psychomotor domains, and involves cross-disciplinary teacher collaboration aimed at nurturing both Islamic character and student professionalism. These results demonstrate that the integrated curriculum at SMK IT Nufat fosters a contextual, collaborative, and transformative approach to PAI learning in a pesantren setting. The study recommends enhancing teacher collaboration, developing systematic tools for character assessment, and expanding value-based instructional models for broader application in vocational education.